1997
DOI: 10.1038/37352
|View full text |Cite
|
Sign up to set email alerts
|

A role for oestrogens in the male reproductive system

Abstract: Oestrogen is considered to be the 'female' hormone, whereas testosterone is considered the 'male' hormone. However, both hormones are present in both sexes. Thus sexual distinctions are not qualitative differences, but rather result from quantitative divergence in hormone concentrations and differential expressions of steroid hormone receptors. In males, oestrogen is present in low concentrations in blood, but can be extraordinarily high in semen, and as high as 250 pg ml −1 in rete testis fluids 1,2 , which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
500
3
15

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 804 publications
(544 citation statements)
references
References 32 publications
26
500
3
15
Order By: Relevance
“…Many studies have underlined the importance of estrogens in male fertility [5,[32][33][34], as demonstrated by the expression of ERs and aromatase in the testis and by the fact that mice lacking either ERa [5] or aromatase [6] show altered spermatogenesis and infertility. However, evidence for a direct action of E 2 on the seminiferous epithelium is still missing, and remarkably genes that are regulated by E 2 through classical ERE sequences remain unknown in the testis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have underlined the importance of estrogens in male fertility [5,[32][33][34], as demonstrated by the expression of ERs and aromatase in the testis and by the fact that mice lacking either ERa [5] or aromatase [6] show altered spermatogenesis and infertility. However, evidence for a direct action of E 2 on the seminiferous epithelium is still missing, and remarkably genes that are regulated by E 2 through classical ERE sequences remain unknown in the testis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has become quite clear now that E2 is an essential hormone in male reproduction (Hess et al 1997(Hess et al , 2001Sharpe 1998). The presence of both ␣ and ␤ estrogen receptors was reported in several cell types of the testis, including both somatic and germ cells (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Lately the role of estrogens in heart and vascular protection and for maintenance of bone mass has also attracted considerable interest (Farhat et al, 1996). Studies of ERa knock-out mice have revealed important functions for estrogens also in the male reproductive system (Hess et al, 1997;Lubahn et al, 1993). Adversely, estrogens have been implicated in development and progression of tumors in breast and endometrium (Ciocca and Fanelli, 1997).…”
Section: Introductionmentioning
confidence: 99%